Promotion and Regulation of Homologous Recombination by DNA Helicases - Colavito, Sierra (2010)
In eukaryotes, homologous recombination (HR) provides an important means to eliminate DNA double-stranded breaks and other chromosomal lesions. Accordingly, failure in HR leads to genomic instability and a predisposition to various cancer types. While HR is clearly beneficial for genome maintenance, inappropriate or untimely events can be harmful. For this reason, HR must be tightly regulated. Several DNA helicases contribute to HR regulation, by way of mechanisms that are conserved from yeast to humans. Mutations in several HR-specific helicases e.g. BLM and RECQ5, are either associated with cancer-prone human syndromes or engender the cancer phenotype in animal models. Therefore, delineating the role of DNA helicases in HR regulation has direct relevance to cancer etiology. Genetic, cytological, biochemical, and other analyses have shown that DNA helicases participate in early or late stages of HR, to disrupt nucleoprotein filaments that harbor the Rad51 recombinase or dissociate the D-loop intermediate made by Rad51, or to prevent undesirable events and/or minimize potentially deleterious crossover products. Moreover, the ensemble that harbors BLM and topoisomerase IIIα can dissolve the double Holliday junction, a complex DNA intermediate generated during HR, to produce non-crossover products. These regulatory pathways function in parallel to promote the usage of the genome-preserving synthesis dependent strand annealing HR pathway or otherwise suppress crossover formation.